Communication Skills for Human Resource Development Centres Pakistan Army - Collage Of Army Education, Upper Topa Muree (GHQ Rawalpindi Army Education Publishing House, 2007)
Discusses communication skills needed in the workplace, including writing concise reports, public speaking, and communicating in meetings and other company settings.
Keywords: Public speaking